System-wide Studies of N-Lysine Acetylation in Rhodopseudomonas palustris Reveal Substrate Specificity of Protein Acetyltransferases - Crosby, Heidi A. (American Society for Biochemistry and Molecular Biology, 2012)
N-Lysine acetylation is a posttranslational modification that has been well studied in eukaryotes and is likely widespread in prokaryotes as well. The central metabolic enzyme acetyl-CoA synthetase is regulated in both bacteria and eukaryotes by acetylation of a conserved lysine residue in the active site. In the purple photosynthetic α-proteobacterium Rhodopseudomonas palustris, two protein acetyltransferases (RpPat and the newly identified RpKatA) and two deacetylases (RpLdaA and RpSrtN) regulate the activities of AMP-forming acyl-CoA synthetases. In this work, we used LC/MS/MS to identify other proteins regulated by the N-lysine acetylation/deacetylation system of this bacterium. Of the 24 putative acetylated proteins identified, 14 were identified more often in a strain lacking both deacetylases. Nine of these proteins were members of the AMP-forming acyl-CoA synthetase family. RpPat acetylated all nine of the acyl-CoA synthetases identified by this work, and RpLdaA deacetylated eight of them. In all cases, acetylation occurred at the conserved lysine residue in the active site, and acetylation decreased activity of the enzymes by >70%. Our results show that many different AMP-forming acyl-CoA synthetases are regulated by N-lysine acetylation. Five non-acyl-CoA synthetases were identified as possibly acetylated, including glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and Rpa1177, a putative 4-oxalocrotonate tautomerase. Neither RpPat nor RpKatA acetylated either of these proteins in vitro. It has been reported that Salmonella enterica Pat (SePat) can acetylate a number of metabolic enzymes, including GAPDH, but we were unable to confirm this claim, suggesting that the substrate range of SePat is not as broad as suggested previously.